Integrated Assessment of Organochlorine Pesticide Residues in Soil and Pepper: Ecological and Human Health Risks - M. B. Adekola; A. M. Taiwo; B. S. Bada; T. M. Oladipo; N. A. Amusa; A. A. Alli; J. O. Alabi; M. F. Olorunnishola; E. N. Danton; S. T. Idowu; Z. O. Afolabi; A. A. Awujoola; et al. (CLEAN – Soil, Air, Water, 2026)
ABSTRACT This study investigated organochlorine pesticide (OCP) residues in agricultural soils and pepper samples to assess their ecological and human health risks. Eighty soil samples (pre‐[40] and post‐[40] pesticide application) and 40 pepper samples were analysed using gas chromatography–mass spectrometry. Bioaccumulation factors (BAFs), health and ecological risk assessments were carried out. Before pesticide application, soils already contained detectable OCP residues, particularly α‐BHC (5.0–5.3 µg/kg) and γ‐HCH (7.7–9.3 µg/kg), indicating background contamination. Following pesticide application, residue levels increased significantly ( p < 0.05), with endosulfan sulfate (1789.88 µg/kg) and endrin (161.33 µg/kg) reaching the highest concentrations at contamination hotspots resulting in ecological risk quotients that exceeded guideline thresholds. Pepper samples showed substantial bioaccumulation of OCPs, confirming their transfer from soil into edible crops. The highest BAFs were recorded for 4,4′‐DDE (11,168.62), dieldrin (5180.07), 4,4′‐DDT (5164.89), and endosulfan I (1645.27). Health risk assessment indicated that most non‐carcinogenic risks for adults were within acceptable limits, although dieldrin exceeded the safety threshold (HQ = 1.35). Children were more vulnerable, with hazard quotient values exceeding 1.0 for several pesticides, including dieldrin (13.46), 4,4′‐DDE (5.36), aldrin (2.71), endrin aldehyde (2.47), and heptachlor epoxide (1.27). Cancer risks ranged from 2.21 × 10 − 6 to 5.27 × 10 − 4 for adults and 4.51 × 10 − 5 to 1.08 × 10 − 2 for children, with dieldrin and aldrin posing the greatest concern. These findings revealed persistent OCP contamination, pronounced spatial variability, and high BAF values in peppers, highlighting elevated ecological risks and greater health risks for children.